Advanced Technologies, Systems, and Applications II Proceedings of the International Symposium on Innovative and Interdisciplinary Applications of Advanced Technologies (IAT) /: Proceedings of the International Symposium on Innovative and Interdisciplinary Applications of Advanced Technologies (IAT). (2018) - Unknown
No abstract available